Teleworking in Portuguese public administration during the COVID-19 pandemic: Advantages, disadvantages, work-life balance and motivation. (17th October 2022) - Madureira, César; Rando, Belén
Abstract : This article seeks to characterise teleworking in public administration during the COVID-19 pandemic. It draws on a study that aimed to collect the perceptions of Portuguese public servants about this phenomenon. Findings show that, in general, perceptions of workers and managers about teleworking are more positive than negative. It seems that teleworking in public administration has succeeded despite perceptions of insufficient equipment supply and some stigmatisation of teleworkers. The article also sought to investigate whether the perception of the potential advantages and disadvantages of teleworking, with special emphasis on work-life balance, varies according to the workers' gender and number of dependents. The study found that this was indeed the case. However, there were also differences relating to workers' motivation. The study found that a significant proportion of Portuguese public servants felt more motivated when performing their activities as teleworkers.